2020
DOI: 10.1007/s11244-020-01329-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Nature of the Promoter in NiO Catalysts on the Selectivity to Olefin During the Oxidative Dehydrogenation of Propane and Ethane

Abstract: A comparative study of the catalytic properties for the oxidation of C2-C3 alkanes and olefins has been carried out over unpromoted and M-promoted NiO catalysts (Me= K, La, Ce, al, Zr, Sn, Nb). The catalysts have been characterized by several physicochemical techniques (UV Raman, Visible Raman, FTIR of adsorbed CO and XPS). The characteristics of promoter elements are of paramount importance, since they are able to modify both the nature of the active nickel and the concentration of electrophilic O2 -/Ooxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…4). Furthermore, in previous comparative studies of undoped and Zr-or Nb-doped NiO catalysts for ethane ODH at 350 °C, it was observed that the r C2H4 /r C2H6 ratio shows small differences between 0.41 and 0.53 [62], similar to that reported here. However, supported vanadium oxide catalysts present r C2H4 /r C2H6 ratios between 2 and 10, depending on the hydrocarbon feed and the support [16].…”
Section: Catalytic Resultssupporting
confidence: 90%
“…4). Furthermore, in previous comparative studies of undoped and Zr-or Nb-doped NiO catalysts for ethane ODH at 350 °C, it was observed that the r C2H4 /r C2H6 ratio shows small differences between 0.41 and 0.53 [62], similar to that reported here. However, supported vanadium oxide catalysts present r C2H4 /r C2H6 ratios between 2 and 10, depending on the hydrocarbon feed and the support [16].…”
Section: Catalytic Resultssupporting
confidence: 90%
“…As suitable catalysts for ODH of short alkanes, especially propane, mainly vanadia but also NiO- and boron-oxide-based catalysts have been discussed. ,, In particular, catalysts with amorphous surface vanadia species (VO x ) as the active phase have shown promising performances during propane ODH, but further catalyst optimization is still required. , Besides the active phase, the choice of the support material is of great importance and has been proposed to increase the catalytic performance in the case of active support materials such as CeO 2 and TiO 2 due to their direct participation in the reaction. ,, Recently, ceria-supported vanadia (VO x /CeO 2 ) catalysts have attracted increased attention, both theoretically and experimentally. ,,,, Nevertheless, direct experimental insight into the reaction intermediates and the surface dynamics have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Doping NiO with heteroatom, such as, Nb, Al, Sn, Ti, and W, has been reported to improve the selectivity of alkenes. [25,26] It has been suggested that electronic structure change due to solid solution formation resulted in the reduced concentration of the electrophilic O species [27] and suppressed further oxidation of alkene. Although these studies demonstrated the improvement of selectivity and yield of alkene by modifying NiO, how the modification affects the ODH mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%